2008
DOI: 10.1016/j.tate.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Using an analogy in the introduction of a portfolio

Abstract: Students in many teacher education programmes experience confusion about portfolios. This study investigated whether using an analogy in the introduction of a portfolio helps teacher education students understand both the purpose of a portfolio and how to compile it. It was also investigated whether these students' understanding correlates with their appreciation of portfolios. In the analogy, portfolios were compared with job application letters, curricula vitae and the references that are common in selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Here, Struyven et al (2014) found that teacher trainers and mentors considered the portfolio a useful instrument in the assessment of teaching competencies. Van Tartwijk, Van Rijswijk, Tuithof, and Driessen (2008) shows that an analogy between portfolio and professional methods, as for example application letters, helped students to understand and appreciate the portfolio model. The third promoting dimension is Critical thinking, as this dimension is fundamental both in academia and in the teaching professions.…”
Section: The Portfolio Modelmentioning
confidence: 99%
“…Here, Struyven et al (2014) found that teacher trainers and mentors considered the portfolio a useful instrument in the assessment of teaching competencies. Van Tartwijk, Van Rijswijk, Tuithof, and Driessen (2008) shows that an analogy between portfolio and professional methods, as for example application letters, helped students to understand and appreciate the portfolio model. The third promoting dimension is Critical thinking, as this dimension is fundamental both in academia and in the teaching professions.…”
Section: The Portfolio Modelmentioning
confidence: 99%
“…Lecturers and people-in-charge are also encouraged to present their research work before the faculty members in order to stress the significance of this issue and to evaluate it. Similar to what Tartwijk and others (Tartwijk et al, 2007) did in their simulate experiment; they compared portfolios to a tool of advancing employees in their work. It might be initiated to launch an academic resource for the members of faculty, which would publicize the members of faculty on the internet, which one of its requests would be a summary of the same portfolio.…”
Section: Summary Discussion and Recommendationsmentioning
confidence: 92%
“…Student teachers finalise each practice period by composing a portfolio to show the level of their professional performance by including documents, videos and evaluations illustrating their abilities (cf. van Tartwijk et al 2008). Student teachers are also supervised by university supervisors, who, amongst others, visit the student teacher periodically at their placement school, provide them with feedback on methods and theory and monitor developmental progress throughout teacher education.…”
Section: Contextmentioning
confidence: 99%